The Relationship Between Scabies Risk Factors and The Incidence of Scabies in Male Santri at Nurul Jadid Islamic Boarding School, Kubu Raya - Azzahra, Jihan (Jurnal Health Sains, 2025)
Scabies is an infectious disease caused by Sarcoptes scabiei variety hominis that spreads through direct or indirect contact. This skin disease is characterized by itching and is easily transmitted from person to person and occurs in boarding schools with a high incidence rate. This study aims to determine the relationship between risk factors for scabies and the incidence of scabies in male students at Pondok Pesantren Nurul Jadid Kubu Raya. Observational analytic research with a cross-sectional type research design approach. The independent variables in this study were lighting, antiseptic use, bed cleanliness, clothing / prayer equipment and towel cleanliness of male students, while the dependent variable in this study was the incidence of scabies at Nurul Jadid Islamic Boarding School Kubu Raya with a total sample of 60 people. The results of Spearman's rho test showed that water hygiene, bed hygiene, clothing hygiene and towel hygiene were associated with the incidence of scabies. There is no relationship between lighting and the use of antiseptics with the incidence of scabies in Nurul Jadid Kubu Raya Islamic Boarding School.